Metabolic complications of childhood obesity - Munusamy, Jeyaraj (J Family Med Prim Care, 2021)
CONTEXT: Childhood obesity is a global health problem. A percentage of 2.3 of Indian boys and 2.5 of Indian girls are obese. Childhood obesity is associated with many morbidities like diabetes mellitus, coronary artery disease, musculoskeletal problems, and increased mortality. AIMS: The aim of this study is to estimate burden of metabolic complications of obesity in child and parents of obese children and compare it with normal-weight children. SETTINGS AND DESIGN: The study was done at a tertiary health center in northern India. It was a cross-sectional study. METHODS AND MATERIAL: We enrolled 60 obese children and age- and sex-matched 26 controls, based on Indian Academy of Pediatrics (IAP)2015 body mass index (BMI) charts. Anthropometric parameters and metabolic complications in family were compared between cases and controls. Clinical markers of metabolic derangements and laboratory metabolic profile were assessed for obese children. STATISTICAL ANALYSIS USED: Descriptive statistics was used to describe frequencies. Chi-square test and Mann–Whitney test and Spearman correlation were used for comparison. RESULTS: The prevalence of obesity and obesity-related complications was high in families of obese children. Ten percent of obese children had impaired fasting glucose and 30% had Haemoglobin A1c (HbA1c) in prediabetes category. Forty percent of obese children had dyslipidemia, 45% had transaminitis, and 46.7 were vitamin D deficient. A percentage of 41.7 of obese children had fatty liver on ultrasound. CONCLUSIONS: The family health and child weight are linked through home environment and genetics. The metabolic complications of obesity prediabetes, dyslipidemia, fatty liver, and lower vitamin D level are common in childhood obesity. Regular screening and interventions of metabolic complications are essential for saving child's future health.